The Effectiveness of Glyciram in Restoring the Functional State of the Liver After Acute Toxic Damage (Texas Journal of Medical Science, 2023)
The effect of glyceram and silibor on the secretion of bile and its ingredients was studied in white sexually mature rats with acute toxic hepatitis. It was established that glyceram has a more pronounced choleretic effect than silibor. Recommend the use of glyceram as a pathogenetic treatment of liver disease.